Effectiveness of antimicrobial photodynamic therapy mediated by butyl toluidine blue in preventing medication-related osteonecrosis of the jaws in rats - Ervolino, Edilson [UNESP]; Olivo, Mariane Bocalon [UNESP]; Toro, Luan Felipe [UNESP]; Freire, Jéssica de Oliveira Alvarenga [UNESP]; Ganzaroli, Vinícius Franzão [UNESP]; Guiati, Isabella Zacarin [UNESP]; Nuernberg, Marta Aparecida Alberton [UNESP]; Franciscon, João Paulo Soares [UNESP]; Ângelo Cintra, Luciano Tavares [UNESP]; Garcia, Valdir Gouveia [UNESP]; Wainwright, Mark; Theodoro, Letícia Helena [UNESP] (Elsevier, 2022)
Background: Medication-related osteonecrosis of the jaws (MRONJ) is difficult to treat, therefore, prevention would be the ideal clinical approach. This study evaluated the effectiveness of antimicrobial photodynamic therapy (aPDT), mediated by butyl toluidine blue (BuTB) in the prevention of MRONJ-like lesions after tooth extraction in rats. Methods: Twenty-eight senescent female rats were distributed in groups: VEH and VEH-aPDT, treated with vehicle, ZOL and ZOL-aPDT, treated with 100 µg/Kg of zoledronate, both treatments every three days over seven weeks. After three weeks from the commencement of treatment, the mandibular first molar was extracted. For the VEH and ZOL groups, no local treatment was performed, while with the VEH-aPDT and ZOL-aPDT groups, photodynamic treatment was carried out at 0, 2, and 4 days after extraction. For aPDT, 500μl of BuTB solution was deposited on the dental extraction site (0.5 mg/ml; 60 s), followed by irradiation with low-level laser (InGaAIP; 660 nm; 35 mW; 74.2 J/cm²; 60 s). After 28 postoperative days, euthanasia was performed. The hemimandibles were processed to: (1) histological analysis of tissue repair; (2) histometric analysis of the percentage of newly formed bone tissue (PNFBT) and percentage of non-vital bone tissue (PNVBT); (3) immunohistochemical analysis for tartrate-resistant acid phosphatase (TRAP). Results: The ZOL and ZOL-aPDT groups showed less TRAP-positive cells when compared with VEH and VEH-aPDT. The ZOL group demonstrated great compromise in the tissue repair process, consistent with MRONJ-like lesions. VEH, VEH-aPDT and ZOL-aPDT presented a favorable tissue repair process. PNFBT in the ZOL group was lower than in the VEH, VEH-aPDT and ZOL-aPDT groups, whereas PNVBT in the ZOL group was higher than in the VEH, VEH-aPDT and ZOL-aPDT groups. Conclusion: aPDT mediated by BuTB prevented the occurrence of MRONJ-like lesions after tooth extraction in rats.
Keywords: Bisphosphonates; Butyl toluidine blue; Jaws; Osteonecrosis; Photodynamic therapy; Prevention